PROFESSIONAL DEVELOPMENT MANAGEMENT FOR TEACHERS, ESPECIALLY HISTORY TEACHERS - Nedia Lestari Sihombing; Miftahuddin (RADJA PUBLIKA, 2026)
Education is a process of transmitting knowledge and skills while simultaneously fostering human character and personal development. It plays a crucial role in cultivating critical thinking skills among learners. In this context, teachers particularly history teachers serve as key agents in shaping future generations through the transmission of nationalism, the values of national struggle, and collective historical memory. Therefore, the professional development of teachers is essential to ensure engaging and effective learning experiences that achieve educational objectives. In teacher professional development, managerial leadership plays an important role in organizing and supporting teachers, especially those teaching history. In Minahasa Regency, the limited availability of qualified history teachers has resulted in history subjects often being taught by teachers from non-history academic backgrounds. This condition highlights the importance of managerial intervention in addressing challenges in the field. The purpose of this study is to analyze the management of professional development for history teachers in Minahasa Regency. This research employed a descriptive qualitative method through interviews with history teachers, including the core administrators of the History Teachers’ Subject Forum (MGMP Sejarah) in Minahasa Regency. The findings reveal that the role of management is highly fundamental in supporting teacher professional development through systematic data collection, regular supervision, and the active involvement of school principals in fostering collaboration among history teachers in Minahasa. Such collaboration contributes to making history learning more appealing to students while also encouraging critical thinking regarding historical events that embody the values of patriotism, nationalism, and national identity.